The seductions of Scala - Wampler, Dean (O'Reilly, 2010)
"Scala is a hybrid object-functional language for the JVM. Java programmers can easily migrate to Scala as an improved Java, then learn to exploit its powerful support for Functional Programming. Developers from other languages can exploit the JVM's power and rich libraries using a state-of-the-art language. This video shows you why Scala is seductive and why it meets the needs of the modern developer."--Product description page (viewed Oct. 19, 2010).